A method for preparing a magnesium alloy surface ultra-low energy consumption, high corrosion resistance micro-arc oxidation coating
Patent Information
- Application Number
- CN202310160873.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-24
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-02-24
AI Technical Summary
然而,在实践中,微弧氧化电解液组分的调整虽然降低了能耗,往往也降低了膜层的耐腐蚀性能,导致无法满足耐蚀性等应用要求
[0026]1、本发明中的镁合金表面超低能耗、高耐蚀性能微弧氧化涂层的制备方法,核心创造为低能耗微弧氧化电解液和有序调控变频方波脉冲外控电参数控制方法,一方面通过电解液组分优化,降低微弧氧化工作电流、电压,降低氧化能耗,另一方面,通过有序调控变频方波脉冲外控电参数,使微弧氧化的放电阻抗与输入阻抗实现尽可能的匹配,提高能量转化效率和膜层微观结构均匀性,从而提高膜层性能。
Smart Images

Figure BDA0004094090150000051 
Figure BDA0004094090150000061 
Figure BDA0004094090150000071
Abstract
Description
Technical Field
[0001] This invention relates to the field of light metal surface treatment technology, specifically to a method for preparing an ultra-low energy consumption, highly corrosion-resistant micro-arc oxidation coating on a magnesium alloy surface. Background Technology
[0002] Magnesium alloys, as crucial lightweight metal materials, possess excellent properties such as low density, good damping effect, and high specific strength, making them widely used in aerospace, automotive, and modern biomedical fields. Many countries worldwide have recognized the importance of lightweight alloy materials, successively researching and developing them, and achieving practical applications. However, the poor corrosion resistance of magnesium alloys limits their applications. Therefore, it is necessary to treat their surfaces to broaden their application range.
[0003] Currently, plasma electrolytic oxidation (Plasma Electrolytic Oxidation or Micro-arc Oxidation) is a preparation technology for in-situ growth of ceramic oxide films on metal surfaces, and it is one of the most effective means to improve the corrosion resistance of non-ferrous metals such as magnesium alloys. It is a technology that, under the combined action of thermochemistry, plasma chemistry, and electrochemistry, uses a high voltage to introduce the working area from the Faraday region of ordinary anodic oxidation to a high-voltage discharge region, thereby growing a ceramic oxide film in situ on the metal surface. Micro-arc oxidation technology has many advantages such as high hardness, good corrosion resistance, and wide material adaptability, but it also suffers from high energy consumption, leading to high production costs and reducing the technology's applicability. Because micro-arc oxidation is performed under high voltage and high current density, higher requirements are placed on the power and stability of the oxidation power supply when processing large workpieces. Furthermore, the large amount of heat dissipated during micro-arc oxidation necessitates high-power cooling equipment, all of which increase equipment costs. Therefore, achieving low energy consumption in magnesium alloy micro-arc oxidation is key to promoting its development in multiple fields.
[0004] Currently, research on low-energy micro-arc oxidation technology for magnesium alloys mainly focuses on optimizing the electrolyte formulation and reducing the oxidation voltage. Wang Xiaobo (Wang Xiaobo. Research on the Design and Additive Mechanism of Low-Energy Micro-arc Oxidation Electrolyte for Magnesium Alloys [D]. Harbin Institute of Technology, 2012.) developed a low-energy-consumption electrolyte formulation for magnesium alloy micro-arc oxidation. Adding NaF, Na2CO3, and (NaPO3)6 additives to the electrolyte reduced the micro-arc oxidation voltage of magnesium alloys, thereby reducing unit energy consumption. Chen Fei et al. reported in their patent (A Low-Energy Micro-arc Oxidation Method for Magnesium Alloy Surface CN 112144090 A) that by optimizing the electrolyte composition, the working voltage of micro-arc oxidation was reduced from over 300V to below 180V, thus significantly reducing the energy consumption of micro-arc oxidation. However, in practice, while adjusting the composition of the micro-arc oxidation electrolyte reduces energy consumption, it often also reduces the corrosion resistance of the film, resulting in failure to meet application requirements such as corrosion resistance. Therefore, there is an urgent need for a method to prepare an ultra-low energy consumption and highly corrosion-resistant micro-arc oxidation coating on the surface of magnesium alloys, so as to reduce the processing cost of micro-arc oxidation on the surface of magnesium alloys and at the same time enable the micro-arc oxidation coating to have excellent corrosion resistance. Summary of the Invention
[0005] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a method for preparing an ultra-low energy consumption, highly corrosion-resistant micro-arc oxidation coating on the surface of magnesium alloys. This method, on the one hand, optimizes the electrolyte composition to reduce the voltage and current required during micro-arc oxidation, resulting in lower energy compared to ordinary micro-arc oxidation. This allows the plasma to discharge at a lower temperature, preventing excessive grain growth during the micro-arc oxidation film growth process. On the other hand, by orderly controlling the external control parameters of the variable-frequency square wave pulse, the discharge impedance of the micro-arc oxidation is effectively matched. This maximizes the uniformity of plasma discharge while improving energy conversion efficiency, thereby reducing energy consumption and avoiding microscopic defects caused by excessive plasma discharge, thus improving the protective performance of the magnesium alloy substrate.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0007] A method for preparing an ultra-low energy consumption, highly corrosion-resistant micro-arc oxidation coating on a magnesium alloy surface, comprising the following steps:
[0008] (1) Pretreatment of the magnesium alloy substrate surface: The pretreatment is a process of grinding, polishing, degreasing and pickling to remove rust in sequence;
[0009] (2) Prepare a low-energy-consumption micro-arc oxidation electrolyte for magnesium alloys;
[0010] (3) The pretreated magnesium alloy is placed in the prepared electrolyte, and a dense and uniform micro-arc oxidation ceramic film is prepared on the surface of the magnesium alloy substrate by using a novel orderly controlled variable frequency square wave pulse external control electrical parameters.
[0011] In step (1) above, the degreasing is alkaline degreasing or ultrasonic degreasing with organic solvent; the degreasing solution used for alkaline degreasing consists of: 20 g / L sodium hydroxide, 30 g / L sodium phosphate, 10 g / L sodium carbonate, 1 ml / L OP-10, and the remainder is water, with a degreasing temperature of 70-80℃ and a degreasing time of 3-5 min; the ultrasonic degreasing with organic solvent is degreasing with organic solvent under the assistance of ultrasound, and the organic solvent is anhydrous ethanol or anhydrous acetone.
[0012] In step (1) above, the pickling solution used in the pickling and rust removal is nitric acid with a concentration of 10 vol%, and is treated at room temperature for 30 seconds.
[0013] The composition of the low-energy-consumption micro-arc oxidation electrolyte for magnesium alloy is as follows:
[0014] Main film-forming agent: Select one or more of the following: sodium phosphate 10-50 g / L, sodium hexametaphosphate 5-30 g / L, sodium polyphosphate 3-50 g / L, and sodium silicate 2-50 g / L;
[0015] Conductivity regulator: Select one or more of the following: sodium fluoride 1-10 g / L, potassium fluoride 1-15 g / L, ammonium fluoride 1-15 g / L, ammonium bifluoride 1-15 g / L, sodium carbonate 5-30 g / L, and sodium bicarbonate 5-30 g / L.
[0016] Discharge regulator: Select one or more of the following: disodium ethylenediaminetetraacetate 1-10 g / L, sodium aminotriacetate 1-10 g / L, and diethylenetriaminepentacarboxylate 1-5 g / L;
[0017] Surface passivating agent: Select one or more of the following: hexamethylenetetramine 0.1-5 g / L, phenylalanine 0.1-3 g / L, threonine 0.1-3 g / L, sodium alginate 0.1-5 g / L, sodium tetraborate 0.1-5 g / L, sodium metaborate 0.1-5 g / L, and sodium perborate 0.1-5 g / L;
[0018] pH adjuster: Select one or more of the following: sodium hydroxide 1-10 g / L, potassium hydroxide 1-10 g / L, triethylenetetramine 2-50 g / L, and triethanolamine 2-50 g / L;
[0019] Water: Balance.
[0020] In step (3) above, the control process of the external control electrical parameters of the novel ordered control frequency-modulated square wave pulse is as follows:
[0021] During micro-arc oxidation, constant current control is applied before reaching the final voltage, and constant voltage control is applied after reaching the final voltage. As the oxidation voltage increases, the pulse frequency gradually increases, the positive duty cycle remains constant or gradually decreases, and the negative duty cycle remains constant or gradually increases. The pulse frequency ranges from 100 to 1000 Hz, the final positive voltage is 200 to 400 V, the final negative voltage is 10 to 50 V, the positive duty cycle is 50% to 80%, the negative duty cycle is 10% to 40%, and the remainder is the dead zone. The current density ranges from 0.3 to 1 A / dm³. 2 The oxidation time is 5 to 90 minutes; the solution temperature is controlled within 10 to 50 degrees Celsius during the oxidation process.
[0022] The micro-arc oxidation ceramic coating prepared on the surface of a magnesium alloy substrate by the method of the present invention is as follows:
[0023] The oxide film thickness is 5–50 μm. This oxide film is a uniform ceramic film with a porosity of 5%–10% and a neutral salt spray resistance time of 96–1000 h.
[0024] The magnesium alloy matrix is AZ31, AZ91, AZ80, ZK61, MB2, MB8, MB15, ZM5, ZM6 or pure magnesium alloy, etc.
[0025] The advantages and effects of this invention are as follows:
[0026] 1. The preparation method of the ultra-low energy consumption and high corrosion resistance micro-arc oxidation coating on the magnesium alloy surface in this invention is based on the core innovation of a low-energy-consumption micro-arc oxidation electrolyte and an ordered control method for external electrical parameters of variable frequency square wave pulses. On the one hand, by optimizing the electrolyte composition, the working current and voltage of micro-arc oxidation are reduced, thereby reducing oxidation energy consumption. On the other hand, by orderedly controlling the external electrical parameters of variable frequency square wave pulses, the discharge impedance of micro-arc oxidation is matched with the input impedance as much as possible, thereby improving energy conversion efficiency and film microstructure uniformity, and thus improving film performance.
[0027] 2. The low-energy-consumption micro-arc oxidation electrolyte designed in this invention has undergone systematic experimentation and screening of the main film-forming agent, conductivity regulator, discharge regulator, surface passivator, and pH regulator. The role and selection scheme of each solution component have been clarified. This not only effectively reduces the energy consumption of micro-arc oxidation, but also produces a micro-arc oxidation coating with excellent corrosion resistance, which can meet the application requirements of various magnesium alloy surfaces such as AZ31, AZ91, AZ80, ZK61, MB2, MB8, MB15, ZM5, and ZM6.
[0028] 3. The orderly control method for external electrical parameters of variable frequency square wave pulses in this invention gradually increases the pulse frequency as the oxidation voltage increases, while the positive duty cycle remains constant or gradually decreases, and the negative duty cycle remains constant or gradually increases. Compared with the traditional micro-arc oxidation method with a fixed frequency or duty cycle, this method controls the pulse frequency and duty cycle during the oxidation process to match the discharge impedance of micro-arc oxidation with the input impedance, reducing energy loss due to polarization during the oxidation process, improving energy conversion efficiency, and maximizing plasma discharge uniformity. This avoids concentrated plasma spark eruptions that could cause defects such as localized micropores and large cracks in the oxide film, thereby improving the corrosion resistance of the film. Attached image description:
[0029] Figure 1 The image shows the microscopic surface morphology of the micro-arc oxidation coating prepared in Example 1.
[0030] Figure 2 The microscopic surface morphology of the micro-arc oxidation coating prepared in Example 2 is shown.
[0031] Figure 3 The image shows the microscopic surface morphology of the micro-arc oxidation coating prepared in Example 3. Detailed implementation method:
[0032] The present invention will be further described below with reference to embodiments.
[0033] Example 1
[0034] 1. Material preparation: After cutting, grinding and polishing, the AZ31 magnesium alloy is cleaned with ultrasonic cleaning in acetone solution to remove oil and pickling to remove rust, and then washed with deionized water for later use.
[0035] 2. Preparation of magnesium alloy micro-arc oxidation electrolyte:
[0036] Main film-forming agents: sodium phosphate 20g / L, sodium hexametaphosphate 5g / L, sodium silicate 5g / L;
[0037] Conductivity modifiers: sodium fluoride 10 g / L, sodium carbonate 5 g / L;
[0038] Discharge regulator: Disodium ethylenediaminetetraacetate 2 g / L;
[0039] Surface passivating agents: hexamethylenetetramine 1g / L, sodium tetraborate 1g / L;
[0040] pH adjuster: Sodium hydroxide 2g / L, triethylenetetramine 10g / L;
[0041] The rest is deionized water.
[0042] 3. Preparation of micro-arc oxidation ceramic films:
[0043] A magnesium alloy substrate (as the anode) was placed in an electrolyte, and a stainless steel plate was used as the cathode. A dense and uniform micro-arc oxidation ceramic film was prepared on the surface of the magnesium alloy substrate using an ordered control method of externally controlled electrical parameters via variable frequency square wave pulses. The changes in externally controlled electrical parameters with oxidation voltage are shown in Table 1 below.
[0044]
[0045] The total oxidation time was 15 minutes, and the electrolyte temperature was 30–40°C. The micro-arc oxidation coating obtained in this embodiment has a thickness of 10 μm. This oxide film is a uniform ceramic film with a porosity of 5% and a pore size of 0.5–1 μm. The surface morphology is shown in the attached figure. Figure 1 As shown. The adhesion between the coating and the substrate was greater than 20 MPa, and the resistance to neutral salt spray test exceeded 192 hours.
[0046] Example 2
[0047] 1. Material preparation: After cutting, grinding and polishing, the MB15 magnesium alloy is cleaned with ultrasonic in acetone solution to remove oil and pickling to remove rust, and then rinsed with deionized water for later use.
[0048] 2. Preparation of magnesium alloy micro-arc oxidation electrolyte:
[0049] Main film-forming agents: sodium phosphate 5g / L, sodium silicate 15g / L;
[0050] Conductivity modifiers: Sodium fluoride 5g / L, sodium carbonate 10g / L;
[0051] Discharge regulator: Sodium nitrilotriacetate 2g / L;
[0052] Surface passivating agent: hexamethylenetetramine 2g / L;
[0053] pH adjuster: Triethanolamine 20g / L;
[0054] The rest is deionized water.
[0055] 3. Preparation of micro-arc oxidation ceramic films:
[0056] A magnesium alloy substrate (as the anode) was placed in an electrolyte, and a stainless steel plate was used as the cathode. A dense and uniform micro-arc oxidation ceramic film was prepared on the surface of the magnesium alloy substrate using an ordered, variable-frequency square wave pulse external control electrical parameter control method. The changes in external control electrical parameters with oxidation voltage are shown in Table 2 below.
[0057]
[0058] The total oxidation time was 26 minutes, and the electrolyte temperature was 30–40°C. The micro-arc oxidation coating obtained in this example had a thickness of 20 μm. This oxide film was a uniform ceramic film with a porosity of 7% and a pore size of 0.5–1.5 μm. The surface morphology is shown in the attached figure. Figure 2 As shown. The adhesion between the coating and the substrate was greater than 20 MPa, and the resistance to neutral salt spray test exceeded 336 hours.
[0059] Example 3
[0060] 1. Material preparation: After cutting, grinding and polishing, ZM5 magnesium alloy is cleaned with ultrasonic in acetone solution to remove oil and pickling to remove rust, and then washed with deionized water for later use.
[0061] 2. Preparation of magnesium alloy micro-arc oxidation electrolyte:
[0062] Main film-forming agents: Sodium hexametaphosphate 20g / L, sodium silicate 20g / L;
[0063] Conductivity modifiers: potassium fluoride 5g / L, sodium bicarbonate 50g / L;
[0064] Discharge regulator: Diethylenetriamine pentacarboxylate 2 g / L;
[0065] Surface passivating agents: hexamethylenetetramine 1g / L, sodium perborate 2g / L;
[0066] pH adjuster: Sodium hydroxide 2g / L, triethanolamine 20g / L;
[0067] The rest is deionized water.
[0068] 3. Preparation of micro-arc oxidation ceramic films:
[0069] A magnesium alloy substrate (as the anode) was placed in an electrolyte, and a stainless steel plate was used as the cathode. A dense and uniform micro-arc oxidation ceramic film was prepared on the surface of the magnesium alloy substrate using an ordered, variable-frequency square wave pulse external control electrical parameter control method. The changes in external control electrical parameters with oxidation voltage are shown in Table 3 below.
[0070]
[0071] The total oxidation time was 40 minutes, and the electrolyte temperature was 30–40°C. The micro-arc oxidation coating obtained in this example has a thickness of 30 μm. This oxide film is a uniform ceramic film with a porosity of 9% and a pore size of 0.5–2 μm. The surface morphology is shown in the attached figure. Figure 3 As shown. The adhesion between the coating and the substrate was greater than 20 MPa, and the resistance to neutral salt spray test exceeded 600 hours.
Claims
1. A method for preparing an ultra-low energy consumption, highly corrosion-resistant micro-arc oxidation coating on a magnesium alloy surface, characterized in that: The method includes the following steps: (1) Pretreatment of the magnesium alloy substrate surface: The pretreatment is a process of grinding, polishing, degreasing and pickling to remove rust in sequence; (2) Prepare a low-energy-consumption micro-arc oxidation electrolyte for magnesium alloys; The composition of the low-energy-consumption micro-arc oxidation electrolyte for magnesium alloy is as follows: Main film-forming agent: Select one or more of the following: sodium phosphate 10-50 g / L, sodium hexametaphosphate 5-30 g / L, sodium polyphosphate 3-50 g / L, and sodium silicate 2-50 g / L; Conductivity regulator: Select one or more of the following: sodium fluoride 1~10g / L, potassium fluoride 1~15g / L, ammonium fluoride 1~15g / L, ammonium bifluoride 1~15g / L, sodium carbonate 5~30g / L, and sodium bicarbonate 5~30g / L; Discharge regulator: Select one or more of the following: disodium ethylenediaminetetraacetate 1~10g / L, sodium aminotriacetate 1~10g / L, and diethylenetriaminepentacarboxylate 1~5g / L; Surface passivating agent: Select one or more of the following: hexamethylenetetramine 0.1~5 g / L, phenylalanine 0.1~3 g / L, threonine 0.1~3 g / L, sodium alginate 0.1~5 g / L, sodium tetraborate 0.1~5 g / L, sodium metaborate 0.1~5 g / L, and sodium perborate 0.1~5 g / L; pH adjuster: Select one or more of the following: sodium hydroxide 1-10 g / L, potassium hydroxide 1-10 g / L, triethylenetetramine 2-50 g / L, and triethanolamine 2-50 g / L; Water: Balance; (3) The pretreated magnesium alloy is placed in the prepared electrolyte, and the external control parameters of the variable frequency square wave pulse are controlled in an orderly manner to prepare a dense and uniform micro-arc oxidation ceramic film on the surface of the magnesium alloy substrate. The orderly regulation and control process of the external control electrical parameters of the variable frequency square wave pulse is as follows: During the micro-arc oxidation process, constant current control is applied before the final voltage is reached, and constant voltage control is applied after the final voltage is reached. As the oxidation voltage increases, the pulse frequency gradually increases, the positive duty cycle remains unchanged or gradually decreases, and the negative duty cycle remains unchanged or gradually increases. The pulse frequency is 100-1000Hz, the final positive voltage is 200-400V, the final negative voltage is 10-50V, the positive duty cycle is 50-80%, the negative duty cycle is 10%-40%, and the remainder is the dead zone. Current density 0.3~1A / dm 2 The oxidation time is 5 to 90 minutes; the solution temperature is controlled within 10 to 50 degrees Celsius during the oxidation process.
2. The method for preparing an ultra-low energy consumption, highly corrosion-resistant micro-arc oxidation coating on a magnesium alloy surface according to claim 1, characterized in that: In step (1), the degreasing is alkaline degreasing or ultrasonic degreasing with organic solvent; the degreasing solution used for alkaline degreasing consists of: 20 g / L sodium hydroxide, 30 g / L sodium phosphate, 10 g / L sodium carbonate, 1 ml / L OP-10, and the remainder is water, with a degreasing temperature of 70~80℃ and a degreasing time of 3~5 min; the ultrasonic degreasing with organic solvent is degreasing with organic solvent under the assistance of ultrasound, and the organic solvent is anhydrous ethanol or anhydrous acetone.
3. The method for preparing an ultra-low energy consumption, highly corrosion-resistant micro-arc oxidation coating on a magnesium alloy surface according to claim 1, characterized in that: In step (1), the pickling solution used in the pickling and rust removal is nitric acid with a concentration of 10 vol%, and is treated at room temperature for 30 seconds.
4. The method for preparing an ultra-low energy consumption, highly corrosion-resistant micro-arc oxidation coating on a magnesium alloy surface according to claim 1, characterized in that: The micro-arc oxidation ceramic coating prepared on the surface of a magnesium alloy substrate by this method is as follows: The oxide film thickness is 5-50 μm. This oxide film is a uniform ceramic film with a porosity of 5%-10% and a neutral salt spray resistance time of 96-1000 h.
5. The method for preparing an ultra-low energy consumption, highly corrosion-resistant micro-arc oxidation coating on a magnesium alloy surface according to claim 1, characterized in that: The magnesium alloy matrix is AZ31, AZ91, AZ80, ZK61, MB2, MB8, MB15, ZM5, or ZM6.
Citation Information
Patent Citations
Magnesium alloy surface low-energy-consumption micro-arc oxidation method
CN112144090A
Solutions for preparing highly corrosion-resistant self-sealing ceramic coatings on magnesium alloy surfaces and their applications
CN102268710A
Preparation method of low-porosity micro-arc oxidation film on surface of magnesium alloy
CN111172577A